Online cooperative printing by mobile robots - Alhijaily, Abdullah (2024)
Cooperative printing, where multiple printheads concurrently print a part, significantly improves printing speed. However, current literature only discussed offline path planning, in which the toolpaths are generated before the printing process starts. Offline path planning is unreliable and leads to collisions for systems with uncertainties such as mobile robots. In this paper, we developed several online path planning algorithms for cooperative printing by mobile robots that allow toolpath allocation in real time. Unlike offline path planning, it is not possible to replan the layer in case of collision in online systems. Thus, we developed a novel algorithm that guarantees collision avoidance in real time. The system was evaluated through both simulations and experiments. The mobile robots cooperatively printed several layers which showed that the system can significantly increase the speed of 3D printing. This work stands as the first in the literature that allows online path planning for cooperative printing.